EFFECTIVE TEACHING METHODS OF FOREIGN LANGUAGESTHROUGH CULTURAL MEANS - Nurmuradova Ibragimovna, Shakhnoza (International Journal of Psychosocial Rehabilitation, 2020)
This article deals with the effective usage of poetry and songs during practical lessons of teaching foreign languages, particularly Russian. Different ways of using authentic poems and music as a means of learning the original second language are worked out. Besides, it is given a number of suggestions on how to create various tasks and activities while learning any foreign language through lyrics and music for arising intercultural awareness.